Important Role SMK To Optimally Implement Technical and Vocational Education And Training (TVET) - Sri Sarjana; Sartono Sartono; Nur Khayati; Praswiyati Praswiyati; Lis Warini (Universitas Sebelas Maret, 2019)
Technical and vocational education and training (TVET) has important role in supporting the success of vocational education. Vocational school as an education at secondary level has not been able to implement programs and plans that exist in TVET concept. Need for assistance in the implementation of TVET in vocational schools aims to ensure that implementation TVET is not misdirected and is not wrong destination. This research survey was conducted on SMK students in Bekasi district by taking random sample. Verification analysis is performed to hypothesis testing on the influence between variables using structural equation modeling. This study empirically examines the important role of TVET based on preparation, implementation and competency so that it can have an impact on the relevance of knowledge and skills produced. Results of this study stated that preparation, implementation and competency had a significant influence on TVET impact which was applied to vocational students. TVET impacts can be felt by vocational students include relevant to current work, use of skills, utilization of knowledge, results of training, adequate living needs, results of assessments. This research is expected to be used as suggestion for development of quality for SMK as vocational schools at secondary education level can be aligned with objectives of TVET.